Indians and the Environment: An Examination of Jurisdictional Issues Relative to Environmental Management - Schnidman, Frank (Columbia Journal of Environmental Law, 2019)
Since the beginning of the nation, the states, the federal government and the Indian tribes have all vied for jurisdiction over Indian lands. In recent times, heightened concerns for environmental quality and natural resource management have accentuated the conflicting jurisdictional claims. The most troublesome issues are: the extent of permissible Indian initiative to define, regulate and monitor resource management on Indian lands; the interplay between federal regulatory programs and the state and tribal jurisdictional conflicts; and the role of state police power over Indian lands. This article will consider first the tribal, federal and state jurisdictional claims over Indians and Indian land from a historical perspective. The next section examines state administration of environmental management programs on Indian lands. The final section proposes an intergovernmental mechanism to deal with the use, protection, preservation and enhancement of the finite resources on Indian lands.